Implementation of Project-Based Learning in Renewable Energy Materials: Analysis of Implementation and Its Impact on Students’ 21st Century Skills - Puspitasari, Ratna (Scientica Education Journal, 2025)
The urgency of renewable energy education has become increasingly important in developing students' 21st-century skills and environmental awareness. Project-Based Learning (PjBL) emerges as an innovative pedagogical approach that can effectively integrate theoretical knowledge with practical implementation in renewable energy topics. This study aims to analyze the implementation of Project-Based Learning in renewable energy materials and examine its impact on students' 21st-century skills development, particularly critical thinking, creativity, collaboration, and environmental consciousness. This qualitative descriptive study employs a multiple case study approach, analyzing various implementations of PjBL in renewable energy education across different educational levels. Data were collected through document analysis, observation records, and implementation reports from 15 selected studies representing diverse contexts of PjBL application in renewable energy materials. The analysis reveals that PjBL implementation in renewable energy materials consistently enhances students' conceptual understanding, critical thinking skills, creativity, and collaboration abilities. Integration with STEM/STEAM approaches and ethnoscience further enriches the learning experience and increases local relevance. Key success factors include innovative learning media development, hands-on projects, and systematic teacher training. Project-Based Learning proves to be highly effective in renewable energy education, significantly improving both cognitive and affective learning outcomes. However, successful implementation requires systematic support including teacher training, appropriate learning resources, and institutional commitment.